Representation of the Meaning of Hope in BTS's 'Permission to Dance' Music Video: A Roland Barthes Semiotic Analysis (Oratio Directa, 2023)
This study examines the representation of hope in BTS's "Permission to Dance" music video. It aims to reveal how BTS conveys hope through denotative, connotative, and mythological meanings. The study applies qualitative content analysis using Roland Barthes' semiotic perspective. Data were collected through documentation of the music video. The findings show that hope is represented through signs such as releasing purple balloons, a magazine containing predictions, removing masks, and dance movements. These signs represent optimism, freedom, peace, and the hope of returning to normal life after the pandemic.
Keywords: Semiotics; Roland Barthes semiotics; Representation of meaning; Hope; Music video